Measuring the Level of Depression, Anxiety and Self Esteem Among Working and Non-Working Married Women of Sindh Province - Aqsa Kalhoro, Abdul Razzaque Nohri, Sajan, Muhammad Ali Memon, Bakhat Ali Siyal, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Depression is one of the common disabilities which is difficult to treat, hence an interesting as well as difficult to research. However, depression can be managed. The management will still a number of challenges, like failure to cut back and reoccurrence. One who has the ability to face and fight threats and weakness, and having self-satisfaction are the signs of high self-esteem. Objective: The objective of the study was to assess the level of depression, anxiety and self-esteem, among working and non-working married women of Sindh Province. This study is of great significance that it was not done before in the proposed area, where there is a crystal-clear depression and self-esteem variation in working v/s non-working women. Study design: An analytical cross-sectional study Place and Duration: Sindh Province from January to June 2022 Methodology: The research was conducted on the pre-developed questionnaire. There was a sample size of (N=67) that was collected from working and non-working women of Sindh Province Pakistan. For measuring the level of depression and anxiety, the Kessler Psychological Distress Scale (K10) scale was used for the measurement of Self-Esteem, Rosenberg Self-Esteem Scale was used among all participants. Consent was taken from all the participants of the study. For statistical data analysis, T-tests and ANOVA were used on SPSS. Results: In this study out of 67 women 47.8% were working and 52.2% were not working. Regarding psychological well-being 27% of women had severe psychological distress, 25% had moderate psychological distress, 30% were psychologically well and 18% had mild psychological distress Conclusion: The findings showed that working women have higher self-esteem than non-working women, but that non-working women have higher levels of distress than working women. This research opens the doors for further researching the causes and way forwards for low self-esteem and high distress with different dimensions. Keywords: Depression, Anxiety, Self-esteem, Working, Non-working women, Sindh Province